Media Iklan Video Di Instagram Pada UMKM Mustika Kayu Poncokusumo Malang - Dimas Wahyu Saputra (Jurnal Ekonomi dan Bisnis Digital, 2024)
Mustika Kayu is a business operating in the handicrafts sector. It is located in Dusun III, Desa Poncokusumo, Malang City. The products offered various types of raw materials such as sono wood, mahoni wood, jati wood and glugu wood. Most of the products made from wood are household utensil products such as silks, cutlery, mortars, plates and coasters. The advertising media, that used Instagram and WhatsApp Advertisement media carried out on Instagram were considered less than optimal because it did not have interesting content. This research aimed to provide interesting content, providing complete information by creating advertising media with Sony Vegas Pro to be uploaded in the form of Instagram content reels. This research used the Action Research method which was carried out by distributing questionnaires to 1 owner, 2 marketing experts, 2 multimedia experts, and 5 potential consumers. To measure the effectiveness of the design, the research used the EPIC method (Empathy, Persuasion, Impact, Communication) The results of the research showed that the EPIC Rate score in cycle 2 was 4.6 in 1 namely Impact. This is due to the design of Instagram Reels which are designed to be very attractive and provide complete information regarding the products offered and the messages contained in the content can be conveyed. The conclusion of this research is that Instagram Reels designed with Sony Vegas Pro are very effective as advertising media on Mustika Kayu Instagram. Mustika Kayu is recommended to make design updates with the aim of serving as a reminder to potential customers and consumers.